Strategies to Prevent Healthcare-Associated Infections: Systematic Review - Rashed Alharbi, Majed Sanat; Abdullah Almutairi, Mousa Mulfi; A Alharbi, Bader Abaid; Saud Alharbi, Raed Jurayyad; A Almutairi, Bader Meatag; R Almutairi, Hammad Qnaim (Journal of Neonatal Surgery, 2025)
Healthcare-associated infections (HCAIs) represent a significant public health challenge and are associated with high burdens of illness and death worldwide. According to research, healthcare-associated infections (HCAIs) are estimated to affect seven per hundred hospitalized patients in high-income countries and ten in emerging and low-income countries. The increasing antimicrobial resistance among pathogens worse ns because very few new antimicrobial agents have entered the market. This article highlights different potential approaches to preventing the occurrence of HCAIs. It sets out how hand hygiene has been and continues to be a key preventative measure across the ages. HCAIs can be addressed through several methods, including keeping the hospital environment clean and enacting antibiotic stewardship programs.